Structural, electronic, and thermodynamic properties of TiO2/organic clusters: performance of DFTB method with different parameter sets. Issue 2 (9th September 2020) - Naumov, Vladimir S.; Loginova, Anastasiia S.; Avdoshin, Alexander A.; Ignatov, Stanislav K.; Mayorov, Alexey V.; Aradi, Bálint; Frauenheim, Thomas
Abstract: The clusters of bare TiO2 and TiO2 with linked organic ligands modeling polyorganic composites used as photocatalytic materials were studied using the density functional based tight binding (DFTB) electronic structure method with three parameter sets ( trans3d, tiorg, and matsci ) in comparison with results of B3LYP/6‐31G(d, p) calculations, semiempirical methods PM6 and PM7, and available experimental data. It was found that the highly scalable DFTB method shows results that are close to the B3LYP/6‐31G(d, p) level of theory. The corrected version of the tiorg DFTB parameter set ( tiorg‐smooth ) has better performance for the estimations of structural parameters, whereas the trans3d set better reproduces energies of the composite material formation in polycondensation reactions. Performance of the matsci set is somehow in the middle of the tiorg‐smooth and trans3d sets. The tiorg‐smooth and matsci sets can be used for the studies of adsorption complexes of bare TiO2 clusters. All three DFTB parameter sets well estimate the electronic parameters of clusters (HOMO‐LUMO gap, ionization potential, and dipole moment). DFTB results are closer to the estimates made with DFT (B3LYP/6‐31G(d, p)) than the results of PM6 and PM7 methods. DFTB calculations of large (up to 448 atoms) bare TiO2 and TiO2 /organic clusters (72 structures in total) confirm the robustness and computational efficiency of the method. Abstract : The comparison of 27 bare TiO2 and TiO2 /organic clusters calculated at the DFTB level with results of B3LYP calculations shows that DFTB parameter sets ( tiorg‐smooth, trans3d, and matsci ) describe the structure and properties of clusters (HOMO‐LUMO gap, potential ionization, and electron transfer characteristics) at a level that is close to DFT calculations. In comparison with PM6 and PM7 methods, DFTB demonstrates better performance at describing electronic and thermodynamic properties, as well as at reproducing structures.